Analysis of Aberrantly Spliced Transcripts of a Novel de novo GNAS Mutant in a Male with Albright Hereditary Osteodystrophy and PHP1A - Ham, H.-J.; Baek, K.-H.; Lee, J.-y.; Kim, S. Y.; Mo, E. Y.; Kim, E. S.; Han, J. H.; Moon, S.-d. (Hormone and Metabolic Research, 2015)
Pseudohypoparathyroidism (PHP) is a genetic disorder due to target-organ unresponsiveness to parathyroid hormone (PTH). PHP type 1A (PHP1A) is an autosomal dominant disease characterized by Albright hereditary osteodystrophy (AHO) and PTH resistance caused by defects at the GNAS locus. We analyzed the GNAS gene in a male with typical AHO and elevated PTH levels. We identified a novel de novo heterozygous mutation at the splice donor site in intron-7 (IVS7+1G>A, c.585+1G>A) of the GNAS gene. No GNAS mutations were detected in his parents. Our patient was diagnosed with PHP1A due to a heterozygous de novo mutation in the GNAS gene. Reverse transcriptase (RT) PCR analysis and sequencing revealed that this de novo splice mutation generated alternative splicing errors leading to the formation of 2 mutant transcripts: one with exon-7 deleted, the other with whole intron-7 included. To investigate whether these aberrantly spliced transcripts were stable, we assessed the differential expression of GNAS mRNAs in the proband’s blood by real-time quantitative RT-PCR. In the proband, the relative expression levels of wild-type, exon-7-deleted, and intron-7-included GNAS mRNAs were 0.21, 6.12E-07, and 1.08E-04, respectively, relative to wild-type GNAS mRNA from a healthy control (set at 1.0). This suggests that this novel de novo splicing mutation generates rapidly decaying mutant transcripts, which might affect stimulatory G-protein activity and give rise to this sporadic case. In conclusion, this is an interesting report of aberrantly spliced mRNAs from a de novo splice mutation of the GNAS gene causing PHP1A in a male.
Keywords: Albright hereditary osteodystrophy; pseudohypoparathyroidism; GNAS; de novo; splice mutation; nonsense-mediated mRNA decay (NMD)